DNACPR Decisions: Aligning Law, Guidance, and Practice. (29th April 2022) - Michalowski, Sabine; Martin, Wayne
Abstract: Do not attempt cardiopulmonary resuscitation (DNACPR) decisions are a means to consider in advance the appropriateness of CPR measures if an acute crisis arises. During the COVID-19 pandemic, problems with such decisions, for example the putting in place of DNACPR decisions for all residents of certain care homes, received a lot of attention, prompting a Care Quality Commission (CQC) report with recommendations for improvement. Building on the CQC report, our article addresses a cluster of legal uncertainties surrounding DNACPR decisions, in particular about the grounds for such decisions and the correct procedures for the legally required consultation, including with whom to consult. This article will also analyse commonly used DNACPR forms, as well as the Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) form, which aims to incorporate DNACPR decisions as part of more holistic end-of-life care planning. The analysis shows that all forms exhibit shortcomings in reflecting the legal requirements for DNACPR decisions. We recommend a number of changes to the forms aimed at rendering DNACPR practice compliant with the law and more protective of the person's human rights.